Trends in Server Energy Proportionality. - Ryckbosch, Frederick; Polfliet, Stijn; Eeckhout, Lieven (Computer (00189162), 2011)
Server energy proportionality, as quantified by the proposed EP metric, has improved significantly, from 30-40 percent in 2007 to 50-80 percent today, but much more can be done to move systems closer to ideal.